Створення веб-редактору для архітектур нейронних мереж та їх експорту для deep learning фреймворків - Бекузаров, М. Р.; Спірідонова, У. О. (ХНУРЕ, 2020)
This paper discusses the particular properties of modern architectures of neural networks, that lead to complication in their design and implementation. Modern neural networks have 2 main distinct features - their computation graphs are non-linear and they often consist of repeated blocks. Representing these structures in a programming language is difficult and prone to errors, so a solution to simplify this process was proposed -to develop a graphical editor, which would allow to create, edit, share and even generate codefor a given Deep Learning framework.An interactive visual representation of the network’s architecture as a 2-D graphshould greatly simplify the process of designing a neural network.